A Review: Livestock On-Station and On-Farm Trial - Sodiq, A; Susanto, A (ANIMAL PRODUCTION, 1999)
Scientist working in international livestock research are expected to be familiar with an interdisciplinary systems approach, and to work in multidisciplinary teams. The argument for this approach is that (1) discipline specialists are not equipped to understand the relationships between the components they focus on and the systems as a whole, (2) if the specialist operates in isolation from the other discipline, he/she is operating in isolation from the system and so the results may be irrelevant or, if applied, actually have a deleterious effect on the systems, (3) therefore, the specialist must understand the system through a systems approach, a systems person, or the activities of a team. Applicants hoping to work in international livestock research are expected to have had project experience in the tropics, where the environment, culture, facilities and infrastructure may be very different from that in Northern Europe. The purpose of this course is to familiarize student with the multidisciplinary or interdisciplinary systems approach and to prepare them for their field projects in the tropics. (Animal Production 1(1) : 36-42 (1999).